Respuesta :

Answer:

x ≈ - 5.32, x ≈ 1.32

Step-by-step explanation:

x² + 4x - 7 = 0 ( add 7 to both sides )

x² + 4x = 7

To complete the square

add ( half the coefficient of the x- term )² to both sides

x² + 2(2)x + 4 = 7 + 4

(x + 2)² = 11 ( take the square root of both sides )

x + 2 = ± [tex]\sqrt{11}[/tex] ( subtract 2 from both sides )

x = - 2 ± [tex]\sqrt{11}[/tex]

Thus

x = - 2 - [tex]\sqrt{11}[/tex] ≈ - 5.32 ( to 2 dec. places )

x = - 2 + [tex]\sqrt{11}[/tex] ≈ 1.32 ( to 2 dec. places )

Answer:

x = -5.32, x = 1.32

Step-by-step explanation:

Ok. So to use the Complete the Square method, you divide the middle value by 2 and then square the number you get. This will give:

[tex](x^{2} + 4x + (\frac{4}{2}) ^2) - (\frac{4}{2}) ^2 -7 = 0[/tex]

[tex](x^{2} + 4x + 4) - 4 -7 = 0[/tex]

[tex](x^{2} + 4x + 4) - 11 = 0[/tex]

[tex](x^{2} + 4x + 4) = 11[/tex]      (now factor the left side)

[tex](x + 2)(x + 2) = 11[/tex]

[tex](x + 2)^{2} = 11[/tex]       (now square root both sides)

[tex]\sqrt{(x + 2)^{2}} = \sqrt{11}[/tex]

[tex]x + 2 = \sqrt{11}[/tex]

[tex]x = - 2 +/- \sqrt{11}[/tex]         (+/- = plus or minus)

x = -5.32, x = 1.32

ACCESS MORE